Implementation of Drug Management Policies at One of The Community Health Centers in Brebes Regency - Hanari Fajarini (SOEPRA, 2022)
Abstract: The drug management policy at the Community Health Center is one of the important aspects because will have an impact on the operational costs. Drugs are materials of places for budget leakage, and while the availability of drugs at any time is a demand for health services, efficient management will determine success overall. The purpose of drug management is the availability of drugs whenever needed both in terms of type, quantity and quality efficiently, thus drug management can be used as a process of mobilizing and empowering all available/potential resources to be utilized to realize the availability of drugs at any time needed for effective and efficient operations.This type of research uses a qualitative approach. The research was conducted in Brebes Regency which lasted for 3 (three) months, from March to May 2021. The selection of informants was carried out using the Purposive Sampling technique. The key informants in this study were the pharmacist in charge of the Pharmacy Room, pharmaceutical technical personnel and the person in charge of the Drug Warehouse. The data validation method uses triangulation techniques. In this study, the triangulation method used is source triangulation.The results show that the Health Center in carrying out drug needs planning is carried out 4 (four) times a year by taking drugs every 3 (three) months or quarterly based on the consumption method and the morbidity method. Drug procurement is carried out every 3 (three) months by submitting an LPLO to the District Health Office and District Pharmacy Warehouse. For distribution to service units and service sub-units, each of them goes to the Health Center Warehouse every month. This is following the Decree of the Minister of Health of the Republic of Indonesia Number 1426/Menkes/SK/XI/2002 where the procurement process for the Health Center is carried out at least once every 3 (three) months. The use of drugs at the Health Center is carried out with a series of activities in the form of understanding the contents of the prescription, and packaging the drug which has written information about the rules for using the drug. Information regarding the use of drugs is also provided by officers at the time of handing over drugs to patients so that the possibility of irrational use of drugs can be avoided. The elimination of drugs at the Health Center is by existing procedures, namely the elimination of damaged/expired drugs is carried out by sending an official report on damaged/expired drugs to the District Health Office through the District Pharmacy Warehouse for follow-up, but sometimes the Health Center also destroys drugs by burning/planted by the District Pharmacy Warehouse policy by giving the authority to the Health Center to destroy them.The conclusion of this study is drug management at One of The Community Health Centers in Brebes Regency is implemented based on the Decree of the Minister of Health of the Republic of Indonesia Number 1426/Menkes/SK/XI/2002 about the Management of Public Drugs and Health Supplies; Regulation of Indonesian Health Minister Number 74 of 2016 about Pharmaceutical Service Standards at Health Centers; and Regulation of Indonesian Health Minister Number 26 of 2020 about Amendments to Minister of Health Regulation Number 74 of 2016 about Pharmaceutical Service Standards at Health Centers.Keyword : implementation, policy, drug management, community health centres Abstrak: Kebijakan pengelolaan obat di Puskesmas merupakan salah satu aspek penting dari pelayanan kesehatan di Puskesmas, sebab ketidaktepatan dalam pengadaan dan pengelolaan akan berdampak kurang baik terhadap biaya operasional Puskesmas. Sediaan farmasi merupakan salah satu barang yang berpotensi mengakibatkan kebocoran anggaran, di sisi lain ketersediaan obat setiap saat merupakan tuntutan bagi setiap fasilitas pelayanan kesehatan. Maka dari itu pengelolaan sediaan farmasi yang efesien sangat menentukan keberhasilan secara keseluruhan dari pelayanan kesehatan. Tujuan pengelolaan obat adalah menyediakan obat agar selalu tersedia setiap saat, baik dari segi  jenis, jumlah maupun kualitas obat. Dengan demikian pengelolaan obat dapat digunakan sebagai sebagai proses penggerakan dan pemberdayaan semua sumber daya atau potensi yang dimiliki untuk dimanfaatkan guna mewujudkan ketersediaan obat setiap saat dibutuhkan untuk operasional efektif dan efisien.Jenis penelitian ini menggunakan metode kualitatif. Penelitian dilaksanakan di Kabupaten Brebes yang berlangsung selama 3 (tiga) bulan yaitu pada bulan Maret – Mei 2021. Informan dipilih dengan menggunakan teknik Purposive Sampling. Informan dalam penelitian ini adalah Apoteker Penganggungjawab, Tenaga Teknis Kefarmasian serta Penganggungjawab Gudang Obat Puskesmas. Metode validasi data menggunakan teknik triangulasi.. Pada penelitian kali ini metode triangulasi yang digunakan adalah triangulasi sumber serta triangulasi teori.Hasil menunjukkan bahwa Puskesmas dalam  melaksanakan perencanaan kebutuhan obat dilakukan setiap tahun sebanyak 4 (empat) kali dengan melakukan pengambilan obat pada setiap 3 (tiga) bulan atau triwulan yang berdasarkan metode konsumsi dan metode morbiditas. Pengadaan obat dilakukan setiap 3 (tiga) bulan dengan mengajukan Laporan Pemakaian dan Lembar Permintaan Obat (LPLPO) ke Dinas Kesehatan dan Gudang Farmasi Kabupaten (GFK). Sedangkan untuk pendistribusian ke unit pelayanan  dan sub unit pelayanan  masing-masing mengambil setiap bulannya ke Gudang Obat Puskesmas. Hal ini sesuai dengan Keputusan Menteri Kesehatan RI Nomor 1426/Menkes/SK/XI/2002 dimana proses pengadaan Puskesmas minimal dilakukan setiap 3 (tiga) bulan sekali. Penggunaan  obat di Puskesmas dilakukan dengan serangkaian kegiatan mulai dari pengkajian resep, dispensing, dan Pelayanan Informasi Obat (PIO). Penghapusan obat di Puskesmas sudah sesuai dengan prosedur yang ada yaitu penghapusan obat rusak/kadaluwarsa dilakukan dengan mengirim berita acara obat rusak/kadaluarsa ke Dinas Kesehatan melalui Gudang Farmasi Kabupaten (GFK) untuk ditindaklanjuti. Dalam kondisi tertentu  pihak Puskesmas sendiri yang melakukan pemusnahan obat dengan cara dibakar/ditanam sesuai dari kebijakan GFK dengan memberikan kewenangan terhadap puskesmas untuk memusnahkannya.Kesimpulan dari penelitian ini adalah Pengelolaan obat pada salah satu Puskesmas di Kabupaten Brebes dilaksanakan dengan berdasarkan Keputusan Menteri Kesehatan RI Nomor 1426/Menkes/SK/XI/2002 tentang Pengelolaan Obat Publik dan Perbekalan Kesehatan, Permenkes Nomor 74 Tahun 2016 tenteng Standar Pelayanan Kefarmasian di Puskesmas serta Permenkes Nomor 26 Tahun 2020 tentang Perubahan atas Permenkes Nomor 74 Tahun 2016 tentang Standar Pelayanan Kefarmasian di PuskesmasKata kunci : implementasi. kebijakan, pengelolaan obat, puskesmas